Jersey : Crown Dependency of the United Kingdom; Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2003)
This review of financial sector regulation and supervision in Jersey in the context of the offshore financial center assessment program contains technical advice and recommendations. The report provides a general overview of the financial system, a summary of the assessment findings and the Reports on Observance of Standards and Codes (ROSCs), and the authorities' action plan. It also presents the detailed assessment for banking, insurance, securities, Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT), and company and trust service providers.